Assessing Chemical Environmental Literacy and Sustainable Self-Awareness among Vocational High School Students - Kurniati, Yashinta Suci; Handayani, Sri (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the level and differences of chemical environmental literacy and sustainable self-awareness among vocational high school students based on grade level and gender. A quantitative descriptive-comparative approach was employed involving 100 students from Grades levels. Data were collected using a chemical environmental literacy test and a sustainable self-awareness questionnaire and analysed through descriptive statistics and the Mann–Whitney test. The results showed that most students demonstrated high levels of chemical environmental literacy and sustainable self-awareness, with no significant differences based on grade level, but a significant gender difference in sustainable self-awareness. The study concluded that the implementation of the Merdeka Curriculum and the Adiwiyata Programme positively contributed to strengthening students’ sustainability competencies. The findings imply the need for more reflective and contextual learning strategies to reinforce the affective dimension of sustainability education.